La virtud odontológica - Jorge Alejandro Flórez-R (Universidad de Antioquia, 2005)
There is a deeper relationship beetwen ethic and dentistry that is not ussually seen. Dentistry in its technical, therapeutic and interventional aspect is a practical discipline as it is ethics, although directed to diferent objectives. For both, as for any human activity there is a virtue, an excelence in its execution. The dentist must search for this virtue in every activity he/she perfoms in his profession.